Functional Extracellular Vesicles for Regenerative Medicine. Issue 36 (23rd March 2022) - Kim, Han Young; Kwon, Seunglee; Um, Wooram; Shin, Sol; Kim, Chan Ho; Park, Jae Hyung; Kim, Byung‐Soo
Abstract: The unique biological characteristics and promising clinical potential of extracellular vesicles (EVs) have galvanized EV applications for regenerative medicine. Recognized as important mediators of intercellular communication, naturally secreted EVs have the potential, as innate biotherapeutics, to promote tissue regeneration. Although EVs have emerged as novel therapeutic agents, challenges related to the clinical transition have led to further functionalization. In recent years, various engineering approaches such as preconditioning, drug loading, and surface modification have been developed to potentiate the therapeutic outcomes of EVs. Also, limitations of natural EVs have been addressed by the development of artificial EVs that offer advantages in terms of production yield and isolation methodologies. In this review, an updated overview of current techniques is provided for the functionalization of natural EVs and recent advances in artificial EVs, particularly in the scope of regenerative medicine. Abstract : Extracellular vesicles (EVs) have made a meteoric rise as a safer and more efficacious alternative to cell therapy in the last decade. This review provides an updated overview of current techniques for the functionalization of natural EVs and recent advances in artificial EVs, particularly in the scope of regenerative medicine.